FINDINGS SUFFERING DAUGHTERS ON CHILD MARRIAGE: COMPARATIVE STUDY WEST NUSA TENGGARA PROVINCE AND RIAU ISLANDS PROVINCE, INDONESIA - Achidsti, Ashilly; Maryam Fithriati (Universitas Negeri Yogyakarta, 2024)
The high rate of child marriage in Indonesia makes this country the fourth highest in the world in 2023. This is ironic with the mandate of point five of the Sustainable Development Goals (SDGs). To overcome this problem, this study will compare two regions namely West Nusa Tenggara Province (the highest rates of child marriage in Indonesia) and Riau Island Province (the lowest rate of child marriage). Qualitative methods are used to explore data on the causal factors, the impact of child marriage on girls, and the response of local governments regarding the prevention of child marriage. The results of the study show that the most influential challenge in preventing child marriage is cultural factors. Other factors that also influence are education level, economic conditions, the view that marriage is a solution, and religious interpretation. Child marriage that occurs in West Nusa Tenggara Province and Riau Islands Province has an impact on girls related to reproductive health risks, mental health, loss of access to education, and potential to be a victim of domestic violence. From the comparison of the two regions, the prevention efforts that have been carried out by the local government and those that should be carried out will be mapped.